(untitled) (Research, Society and Development, 2021)
This study analyzed the impacts of a project to migrate the ERP On-Premises system of a large Brazilian company in the construction industry to Cloud Computing servers, analyzing the main Cloud Computing modalities available in the Brazilian market and which is the best migration alternative for the current scenario of the company. The research methodology of this work is based on the exploratory and descriptive character with the collection of information through bibliographic literature research, documentary research and case studies with data collection through direct and indirect documentation and qualitative analysis of the material with the objective to identify the main challenges related to the implementation of ERP systems in cloud computing. The results obtained from the research carried out indicated that the investment in on-premises servers brought better results and computational performance at the company’s current moment. As final considerations, it can be analyzed that carrying out a POC proved to be essential to expose the various problems that could occur during the project, proving to be of paramount importance for a more assertive decision-making, where it was possible to verify that the assertive choice A Cloud Computing delivery methodology that aligns with the results expected by the business is essential for the success of the ERP migration project.